REALITY AS AN OBJECT OF TRANSLATION (ON THE EXAMPLE OF THE NOVEL "WAY OF ABAI") - Saparbayeva, N.B.; Wen, Jiang; Nurzhayeva, A.M. (Journal of Oriental Studies, 2023)
The novel "The Way of Abai" is a unique novel that revealed to the Chinese reader the life and culture of the Kazakh people. The purpose of this article is to consider realities as an object of translation on the example of Mukhtar Auezov’s priceless novel "The Way of Abai". The analysis of the main methods of translating the realities of Kazakh culture into Chinese is of practical importance for further study within the framework of the theory of translation, as well as such sciences as philology, cultural studies and literary criticism. In order to study this topic, the methods of systemic and comparative analysis, as well as the method of generalization and abstraction, were used. As a result of the analysis, it was revealed that when translating these realities into Chinese, the translator used such translation methods as descriptive translation, transliteration, word substitution and word omission. The research materials can be used as additional literature in the disciplines related to the teaching of translation, languages ​​and literature.